7(2n+5)=9(4n+7)+3

Simple and best practice solution for 7(2n+5)=9(4n+7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2n+5)=9(4n+7)+3 equation:


Simplifying
7(2n + 5) = 9(4n + 7) + 3

Reorder the terms:
7(5 + 2n) = 9(4n + 7) + 3
(5 * 7 + 2n * 7) = 9(4n + 7) + 3
(35 + 14n) = 9(4n + 7) + 3

Reorder the terms:
35 + 14n = 9(7 + 4n) + 3
35 + 14n = (7 * 9 + 4n * 9) + 3
35 + 14n = (63 + 36n) + 3

Reorder the terms:
35 + 14n = 63 + 3 + 36n

Combine like terms: 63 + 3 = 66
35 + 14n = 66 + 36n

Solving
35 + 14n = 66 + 36n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-36n' to each side of the equation.
35 + 14n + -36n = 66 + 36n + -36n

Combine like terms: 14n + -36n = -22n
35 + -22n = 66 + 36n + -36n

Combine like terms: 36n + -36n = 0
35 + -22n = 66 + 0
35 + -22n = 66

Add '-35' to each side of the equation.
35 + -35 + -22n = 66 + -35

Combine like terms: 35 + -35 = 0
0 + -22n = 66 + -35
-22n = 66 + -35

Combine like terms: 66 + -35 = 31
-22n = 31

Divide each side by '-22'.
n = -1.409090909

Simplifying
n = -1.409090909

See similar equations:

| (3x-3)2=23 | | 8x+16-36=2+6(1-x) | | -4.905t^2+10t-45=0 | | 5x^3y-10x^2y^3-40xy^3= | | 2(x-1)+3=-6x+5 | | 32=4(v+4)-2v | | 117(2x-97)=4013 | | (x+8)(x-1)=(2x+5)(x-1) | | 7=5.4+5-3.4x | | 2x^2+19x+35= | | -3m+13-8(m-1)=8m-(2m-4)-9m+1 | | -5(2m-6)=110 | | 3x+24-2x=6 | | X+1x+1+x+2=24 | | -6(3p+3)-44=2(4p+8) | | -(m+4n-9)= | | 80=21+28 | | -114=-6-6(3v+6) | | 3a^2b+6ab^2=e | | 104=8(r+3) | | 4(7v-3)=156 | | 2x+24=12+6 | | (x-2)*180=540 | | 3p^5-24p^4-27p^3= | | -7(8r-5)=-133 | | 3y-147y=0 | | 2(2k+3)+2=11(k+y) | | 8-x=-14 | | -3+13y+8=15+17y-38 | | 175=70+((15+7)*w) | | x^2-4x+21=18 | | 0.8x-0.1(2-2x)=-0.9(x-4) |

Equations solver categories